Kesetaraan Pendidikan Perspektif Rahmah El Yunusiyah - Firmansyah Firmansyah (Program Studi Pendidikan Agama Islam STAI Auliaurrasyidin Tembilahan, 2022)
This research is library research intended to examine whether the educational equality that Rahmah El-Yunusiyah fought for was intended as part of the feminism movement or was Rahmah's thought original and departed from a sociological study of the social facts of society, especially women at that time? The research data is referred to from the results of research related to the thoughts of Rahmah El-Yunusiyah which were published in scientific journals and various reference books relevant to this research. The data in this study were collected through documentation techniques, which were further analyzed inductively. The results of the study in this study indicate that the equality of education for women fought for by Rahmah is a social movement to break traditions in the midst of the Minangkabau community's perception of women's position and rights. According to her, education for women is one of the strategic steps in preparing a better future generation, because of the position of women as the pillar of the household, the first and main teacher for children, which is the foundation in shaping society and the state. Rahmah's thinking departs from her understanding of Islamic teachings and is not part of the feminism movement.